The Effect Of Using Animation Video Youtube Towards Students’ English Vocabulary Mastery At SMA Negeri 2 Tebing Tinggi Academic Year 2021/2022 - Widya Ningsi, Azhary Tambusai (Pusdikra Publishing, 2023)
This research discussed the effect of using YouTube animation videos on students' English vocabulary mastery at SMA Negeri 2 Tebing Tinggi. The formulation of the problem is: for the first time, students usually misinterpret the word, then have difficulty pronouncing it. The objective of this research was: to determine whether or not there was a significant effect and difference on students’ achievement in vocabulary mastery before and after being taught using animated videos. The population were students of grade X SMA Negeri 2 Tebing Tinggi which consisted of two classes. So the sample was grade X MIA 4 consisted of 29 students as the experimental group (using animated youtube videos) and X MIA 1 consisted of 29 students as control groups (without using animated youtube videos). The results in the experimental group showed that the mean value of the pre-test was 69.89 while the average value of the post-test was 78.96. The results in the control group showed that the average value of the pre-test was 55.37 while the post-test was the average test score was 58.51. The results of data analysis, the value of t-test > t-table, where the t-table is 1.674 and the result of the t-test is 7.55 so that the t-test is higher than the t-table. It was concluded that the effect of using youtube animated videos was more significant than the effect without using youtube animated videos on students' vocabulary learning achievement.